2006
DOI: 10.1029/2005gl025336
|View full text |Cite
|
Sign up to set email alerts
|

Impact of anthropogenic forcing on the Asian summer monsoon as simulated by eight GCMs

Abstract: The response of the Asian summer monsoon (ASM) to a transient increase in future anthropogenic radiative forcing is investigated by multi‐model global warming experiments. Most models show that, in Asia, the summer monsoon rainfall increases significantly with global warming. On the other hand, the future change in the large‐scale flow indicates a weakening of the ASM circulation. Enhanced moisture transport over the Asian summer monsoon region, associated with the increased moisture source from the warmer Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
181
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 234 publications
(203 citation statements)
references
References 26 publications
22
181
0
Order By: Relevance
“…The reduced warming of air temperature over Asia than over the tropics, i.e., the negative MTG anomalies in the LGM, is similar to that in a warmer climate (e.g., Ueda et al 2006); however, the fundamental controlling mechanism differs.…”
Section: Sensitivity Experimentsmentioning
confidence: 78%
See 1 more Smart Citation
“…The reduced warming of air temperature over Asia than over the tropics, i.e., the negative MTG anomalies in the LGM, is similar to that in a warmer climate (e.g., Ueda et al 2006); however, the fundamental controlling mechanism differs.…”
Section: Sensitivity Experimentsmentioning
confidence: 78%
“…As was mention in the Introduction, the fundamental driving force of the Asian summer monsoon is the meridional thermal gradient. Ueda et al (2006) investigated projected future change of the Asian summer monsoon under a global warming scenario and found that the convection-induced tropical warming in the middle to upper troposphere exceeds that of the Asian continent. In other words, decrease in the meridional thermal gradient is responsible for the attenuated circulation involved in the Asian monsoon.…”
Section: Discussionmentioning
confidence: 99%
“…Precipitation in China is largely determined by the intensity and duration of the Indian summer monsoon (ISM) and East Asian summer monsoon (EASM). Climate modelling studies show that summer monsoon rainfall in Asia increases significantly with global warming (Ueda et al 2006). The primary cause is an enhanced moisture transport from the surrounding oceans to the Asian continent ( Jiang et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Over the South/East Asian monsoon regions, the intensification of summer monsoon rainfall and its interannual variability have been widely detected within model projections [Hu et al, 2000;May, 2002;Meehl and Arblaster, 2003;Kitoh et al, 2005;Ueda et al, 2006;Annamalai et al, 2007;Lu and Fu, 2010;Turner and Annamalai, 2012]. Based on the Coupled Model Intercomparison Project Phase 3 (CMIP3) multimodel data set, Moise et al [2012] found that the overall Australian summer monsoon precipitation showed little change, but the length of the wet season had increased slightly by the end of 21st century.…”
Section: Introductionmentioning
confidence: 99%